(untitled) (Journal of the College of Basic Education, 2022)
The topic of the research tagged (economic life in Iraq through the book “Dictionary of Countries” by Yaqut Al-Hamawi, d. And the development of his geographical experiences and his start to write his great geographical dictionary, explaining countries and their news, until he settled in the city of Aleppo, where he died after completing his well-known book (Dictionary of Countries).